Integrating Technological Pedagogical Content Knowledge (TPACK) into the Merdeka Curriculum at an elementary school in Parepare: A collaborative approach - Patahuddin; AmpaAndi Tenri; AkibErwin (Proceder: Applied Linguistics, Literature, and Language Education, 2025)
The Merdeka curriculum, applied to all levels of education in Indonesia, is a response to the rapid development of information technology, a current challenge for education in Indonesia. As such, teachers must master Technological Pedagogical Content Knowledge (TPACK) in their teaching process. However, preliminary observations from this study found that none of the English teachers in elementary schools in Parepare could master the eight components of TPACK. This study aims to investigate TPACK’s inclusion in the Merdeka Curriculum for English subjects in elementary schools in Parepare. From January to April 2024, this research involved English teachers. The study reveals that teachers need to gain knowledge in applying TPACK in their teaching, affecting the creativity of their designs for TPACK-based learning materials. The impact of this lack of TPACK mastery is the low interest of students in elementary schools in participating in English language learning. However, the potential benefits of TPACK integration into the curriculum, such as enhanced teacher professional development and improved student outcomes, offer a promising future for education in Parepare. The study contributes to the discourse on TPACK’s role in strengthening teacher professional development and student outcomes in the Merdeka Curriculum.